Transporte coletivo e espaço urbano: contradições, conflitos e mobilização social em João Pessoa-PB - Cabral, Enver José Lopes (2014)
Collective transport is currently managed by private bus companies in João Pessoa. The buses run into the city and have to raise money over the costs of operation, that is, it has to make profit. The spatial distribution of the lines depends on the time and region. The fare, the amount of people standing in crowded buses, the salaries of employees of bus companies, all of this, is subject to the logic of management of the bus service. The aim is to study the bus system, contextualized in urban space and time, realizing that its private management logic and the problems faced are the starting point for understanding the current configuration of the collective transport in João Pessoa. The first chapter presents the bus system in João Pessoa, bringing out the problems that users face on a daily basis, highlighting the link between the problems and spatializations. In Chapter 2 we analyse the problems of the bus service such as overcrowding and the high price of the fare. In Chapter 3 we discussed the process of urbanization in capitalist society, establishing its relationship with the liberal logic of collective transport. In Chapter 4 we will understand the formation of the private logic of collective transport in João Pessoa, getting to know how to set up what today appears as a bus service, with its various inefficiencies. In the last chapter of the dissertation, chapter 5, we analyse the social movements fighting for a public transport, from the protests of June 2013, reflecting on how they relate with the demand for public transport.